Linear algebra and differential equations using MATLAB / Martin Golubitsky; Michael Dellnitz - Golubitsky, Martin
The authors integrate linear algebra, ordinary differential equations, and the computer to help students understand these mathematical concepts, interweaving instructions on how to use MATLAB with examples and theory.